Genomic Diversity and Selection Signatures for Weining Cattle on the Border of Yunnan-Guizhou - Liu, Yangkai; Cheng, Haijian; Wang, Shikang; Luo, Xiaoyv; Ma, Xiaohui; Sun, Luyang; Chen, Ningbo; Zhang, Jicai; Qu, Kaixing; Wang, Mingjin; Liu, Jianyong; Huang, Bizhi; et al. (Frontiers in Genetics, 2022)
Weining cattle is a Chinese indigenous breed influenced by complex breeding and geographical background. The multi-ethnic breeding culture makes Weining cattle requiring more attention as livestock resources for its genetic diversity. Here we used 10 Weining cattle (five newly sequenced and five downloaded) and downloaded another 48 genome data to understand the aspects of Weining cattle: genetic diversity, population structure and cold-adapted performance. In the current study, a high level of genetic diversity found in Weining cattle, and its breed composed by two potential ancestries, which were Bos taurus and Bos indicus. The positive selective sweep analysis in Weining cattle were analyzed using composite likelihood ratio (CLR) and nucleotide diversity (θπ), resulting in 203 overlapped genes. Additionally, we studied the cold adaptation of Weining cattle by compared with other Chinese cattle (Wannan and Wenshan cattle) by three methods (FST, θπ-ratio and XP-EHH). Of the top 1% genes list, UBE3D and ZNF668 were carried out and these genes may be associated with fat metabolism and blood pressure regulation in cold adaptation. Our findings have provided invaluable information for the development and conservation of cattle genetic resources especially in south west China.